The Role of Energy Valuation of Agroforestry Biomass on the Circular Economy - Yarima Torreiro (Energies, 2020)
The use of biomass has increased significantly in recent years. In this context, the use of not valued high-potential biomass (NVHPB) is emerging as a suitable alternative. This is the case of pruning vine, pruning kiwi, scrub (heather, gorse, broom) and forest pruning. The objective of this research was to study the potential of six selected agroforestry biomasses as biofuels in thermochemical processes. For that purpose, biomass was collected by specific machinery. Proximate and ultimate analyses were carried out as well as the inorganic compounds’ determination. Then, natural and forced drying were conducted. Low heating values (LHV) between 17 and 20 MJ/kg (dry basis) were achieved in all analyzed cases. Granulometric reduction, biomass classification and densification took place. Finally, energy recovery tests through microcogeneration were carried out. Values close to 97% in cogeneration efficiency were reached (9% net electric yield and 88% thermal yield), offering an alternative to obtain clean energy.